Extraintestinal manifestations in Crohn's disease and ulcerative colitis: results from a prospective, population-based European inception cohort. (March 2014) - Isene, Rune; Bernklev, Tomm; Høie, Ole; Munkholm, Pia; Tsianos, Epameonondas; Stockbrügger, Reinhold; Odes, Selwyn; Palm, Øyvind; Småstuen, Milada; Moum, Bjørn
Abstract Background. In chronic inflammatory bowel disease (IBD) (Crohn's disease [CD] and ulcerative colitis [UC]), symptoms from outside the gastrointestinal tract are frequently seen, and the joints, skin, eyes, and hepatobiliary area are the most usually affected sites (called extraintestinal manifestations [EIM]). The reported prevalence varies, explained by difference in study design and populations under investigation. The aim of our study was to determine the prevalence of EIM in a population-based inception cohort in Europe and Israel. Methods. IBD patients were incepted into a cohort that was prospectively followed from 1991 to 2004. A total of 1145 patients were followed for 10 years. Results. The cumulative prevalence of first EIM was 16.9% (193/1145 patients) over a median follow-up time of 10.1 years. Patients with CD were more likely than UC patients to have immune-mediated (arthritis, eye, skin, and liver) manifestations: 20.1% versus 10.4% (p < 0.001). Most frequently seen was arthritis which was significantly more common in CD (12.9%) than in UC (8.1%), p = 0.01. Pan-colitis compared to proctitis in UC increased the risk of EIM. Conclusion. In a European inception cohort, EIMs in IBD were consistent with that seen in comparable studies. Patients with CD are twice as likely as UC patients to experience EIM, and more extensive distribution of inflammation in UC increases the risk of EIM.